The essence of life in As-Sa'di tafsir: A multidimensional analysis of Al-Hayah in the Qur'an - Sumardianto, Eko; Azizah, Alfiyatul; Dahliana, Yeti (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2024)
In the contemporary era marked by existential and spiritual crises, a deep understanding of the nature of life has become increasingly important. The Qur'an, as the primary source of Islamic teachings, presents the concept of life through the term Al-Hayah. This study examines the meaning of the term Al-Hayah in the Qur'an using a thematic exegesis approach, with a focus on the work of Abdurrahman bin Nashir As-Sa’di, Tafsir As-Sa’di, as the main reference. The research employs a qualitative methodology with a literature review approach, involving the analysis of Qur'anic verses and related interpretations. The aim of the study is to explore and analyze the meaning of the term Al-Hayah, identify key themes, and understand its context and implications within the Qur'anic view. The findings indicate that the term Al-Hayah encompasses physical, eschatological, spiritual guidance, and existential dimensions of life, as well as the relationship between humans and Allah. As-Sa’di’s interpretation of Al-Hayah not only reflects classical understanding but also remains relevant to the context of modern life, making a significant contribution to thematic Qur'anic exegesis and the application of Qur'anic values in daily life.